Sistem Penentuan Status Gizi Balita Menggunakan Metode NaÃ¯ve Bayes Classifier (Studi Kasus Posyandu Anggrek Putih Seblak Desa Kwaron - Chasanah, Nidhaul; Dwi Indriyanti, Aries; Faizah, Arbiati (Inovate, 2022)
Determination of toddler growth and development is very important to do to see if there is a growth disorder of toddlers from an early age by measuring body weight as the best way to assess the nutritional status of toddlers each month so that children's growth and development will be monitored by measuring toddlers and toddlers regularly, body weight and height. Posyandu is useful for providing services to the community about the importance of toddler development and nutritional status quickly and accurately. Therefore, in this research, make a system design as information about the nutritional status of toddlers us.ing th.e NaÃ¯ve Bayes Classifier metod. This method is fairly sample classification metod by assuming the attribute classification. The calculation process using the Naive Bayes Classifier metod to determine the nutritional status of toddlers will go through 6 stages. So each new data will perform a probability with each existing class, the final result is seen from the highest value of this calculation which is used to see the results of determiining the nut.risio.nal th.e te.sted child.ren. Deter.mi.ning th.e nutritional status o. .f. toddlers by inputting age, sex, weight, height with three data on the nutrition categories of children under five, namely thin, normal, fat. System testing was carried out with 83 data on toddlers at Posyandu Anggrek Putih Dsn Seblak, Kwaron Village, each of which 53 toddler data as training data and 30 other toddler data were used for data testing with an accuracy value of 86.66%. Keywords: Determination of Toddler Nutritional Status, Classification, Naive Bayes Classifier